2021
DOI: 10.1111/mec.15998
|View full text |Cite
|
Sign up to set email alerts
|

A globally ubiquitous symbiont can drive experimental host evolution

Abstract: Organisms harbour myriad microbes which can be parasitic or protective against harm.The costs and benefits resulting from these symbiotic relationships can be contextdependent, but the evolutionary consequences to hosts of these transitions remain unclear. Here, we mapped the Leucobacter genus across 13,715 microbiome samples (163 studies) to reveal a global distribution as a free-living microbe or a symbiont of animals and plants. We showed that across geographically distant locations (South Africa, France, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…Prior studies have identified bacterialderived antimicrobial compounds that inhibit Bd growth [12-14, 17, 18]; however, determining overall microbiome community function remains challenging due to the complex web of interactions occurring amongst microbes [17,19]. Microbial taxa can also switch from being inhibitory to promoting pathogen growth based on community composition [19] and in more extreme cases can shift from being beneficial to parasitic (or vice-versa) in processes that may be mediated by host factors [20,21], the abiotic environment [22] or microbial community ecology [23]. As well as their role in defence, microbial communities are important in maintaining host dermal homeostasis [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified bacterialderived antimicrobial compounds that inhibit Bd growth [12-14, 17, 18]; however, determining overall microbiome community function remains challenging due to the complex web of interactions occurring amongst microbes [17,19]. Microbial taxa can also switch from being inhibitory to promoting pathogen growth based on community composition [19] and in more extreme cases can shift from being beneficial to parasitic (or vice-versa) in processes that may be mediated by host factors [20,21], the abiotic environment [22] or microbial community ecology [23]. As well as their role in defence, microbial communities are important in maintaining host dermal homeostasis [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Leucobacter musarum causes severe rectal disease and ultimately death in C. elegans [ 34 ] . Other species of this genus have been found naturally infecting C. elegans [ 35 , 36 ] . For parasite exposures, L. musarum was grown in LB broth at 30°C overnight, and the culture was standardized to OD(600) 0.3.…”
Section: Methodsmentioning
confidence: 99%
“…For parasite exposures, L. musarum was grown in LB broth at 30°C overnight, and the culture was standardized to OD(600) 0.3. The infection exposure plates were prepared by streaking 74 µl of inoculum containing 20% L. musarum and 80% OP50 (standardized to OD(600) 1) onto 5.5 cm NGM plates and incubating at 25°C for 24 h [ 36 ]. Control plates were prepared by spreading a similar amount of OP50 culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed, for example, in contexts as diverse as viral infections (Martinez et al 2014), the autoimmune response (Langan et al 2019), drug therapy (Pryor et al 2019), metabolic dysfunction (Ussar et al 2016), exposure to high temperatures (Xie et al 2013; Howells et al 2016), and chemical toxicity (Coryell et al 2018). Microbes can therefore impact adaptation of host populations to conditions that are apparently unrelated to the host-microbe interaction itself (Martinez et al 2016; Faria et al 2016; Bates et al 2021; Hoang et al 2021). This ability of microbes to modulate host adaptation to various stressors might thus play a fundamental but still poorly understood role in shaping the evolution of host life history and aging.…”
Section: Introductionmentioning
confidence: 99%